PENGELOLAAN LINGKUNGAN HIDUP ATAS KERUSAKAN PERAIRAN SUNGAI SINGINGI AKIBAT PERTAMBANGAN EMAS TANPA IZIN BERDASARKAN HUKUM ADAT DESA KOTOBARU KABUPATEN KUANTAN SINGINGI - Yolan Indrayani; Firdaus Firdaus; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Each region in Indonesia has a comm unity unit that has inhabited the territory ofIndonesia for centuries and has its own distinctive character. This community unit is anorganized community group, has rulers, has their respective customary laws and has their ownwealth in the form of tangible or intangible objects and controls natural resources within theirreach. Indigenous peoples have local wisdom which is the potential and strength in managing aforest area, land, and river. The problem In this case, river management means thatenvironmental management must pay attention to the impact between generations, with wiseuse, effective protection and prevention of impacts that will arise in the future. The impact isgold mining without a permit, the indigenous people around can no longer use the river as theirlivelihood, because it is damaged and polluted. Therefore, this study aims to examine theenvironmental damage caused by PETI (unlicensed gold mining) as well as to analyze what arethe sanctions for those who damage Singi River waters due to PETI and environmentalmanagement carried out by traditional stakeholders. The method used in this research issociological or empirical research, which is a type of research that uses communityassumptions in finding facts that occur in the field to answer an existing problem. , primarydata, secondary data, and tertiary data. Data collection techniques in this study were interviewsand literature review.Keywords: Indigenous Environmental Damage, Kuantan Singingi.